Comparison of freeze-and oven-dried methanolic leaves extracts of piper sarmentosum roxb. to evaluate in vitro cytotoxicity and antioxidant activity of phenolic compounds - Nor Farahiyah binti Ghazali (Kulliyyah Science, International Islamic University Malaysia, 2019)
Breast cancer is among one of the fatal diseases affecting female population around the globe. According to the National Cancer Institute in 2017, it is estimated 252,710 worldwide deaths are due to breast cancer. Therefore, there is a serious need to introduce and develop alternative medicine that works against this disease. Approximately, 60% of currently used anticancer agents are derived from natural sources, including land plants. Malaysia is one of the South East Asian countries which is known for its high diversity of herbal plants distribution. Piper sarmentosum Roxb. which is locally recognized as “Kaduk” is one of medicinal plant that is being used traditionally to treat headache, cough, waist pain, arthritis, menstrual pain and eczema. It is claimed to possess pharmacological properties including anti-inflammatory, antimalarial, antiplasmodial, anti-diabetic, hypoglycemic, antipyretic, antibacterial and antifungal effects. The aims of this study were to identify and quantify the phenolic compounds in P. sarmentosum methanolic leaves extracts of freeze- and oven-dried techniques and to examine their cytotoxicity potential against breast cancer cells, namely MCF-7 and T47D cells. The identification of phenolic compounds was conducted by analyses of total phenolic content, high performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS). For the cytotoxicity analyses, 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging assay, 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) and acridine orange/propidium iodide (AO/PI) assays were carried out. The total phenolic content values obtained were 89.33 mg GAE/g and 45.67 mg GAE/g of dry extract for freeze-, and oven-dried technique respectively. The HPLC result showed a higher concentration of quercetin, naringenin, tannic acid and gallic acid in the freeze-dried compared to oven-dried extract. Meanwhile, LC-MS analysis identified a total of 24 and 17 phenolic compounds from the oven- and freeze-dried extract, respectively. The DPPH assay showed that the freeze-dried extract exhibited antioxidant properties at IC50 of 60.24 μg/mL and no antioxidant activity was found in the oven-dried extract. The freeze-dried extract was selected for further tests due to its high phenolic content and exhibiting antioxidant properties. The MTS assay demonstrated that the extract had IC50 of 28.06 µg/mL and 2.69 µg/mL for MCF-7 and T47D, respectively. The extract had an inhibitory effect on the proliferation of T47D and MCF-7 cells in a reverse manner of treatment concentration and time. The microscopy analyses showed that the extract exerted more prominent changes in the cells morphology, confluence, volume and membrane disruption in the T47D compared to MCF7 cells. The DNA fragmentation assay on both treated cells indicated apoptosis mode of cell death. This study confirmed that the P. sarmentosum leaves methanolic extract contain active phenolic compounds with potent antioxidant and cytotoxic properties against MCF-7 and T47D breast cancer cells.